Consumer Preference Study on Myrtaceae Fruit Collection of Bogor Botanic Gardens - Martiansyah, Irfan; Hariri, Muhammad Rifqi; Mulyani, Melza; Husaini, Iin Pertiwi A; Hidayat, Arief; Rahmawati, Syamsidah (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractMyrtaceae fruit in Bogor Botanic Gardens (BBG) can be potentially developed as a unique and new fruit consumption style. The study aimed to determine the consumer preferences on Myrtaceae fruit. The method used was organoleptic testing, including a description, hedonic and rank tests. The parameters measured in this study are taste, color, flavor, texture, sound, and size of the fruit. Data analysis performed by the Kruskal-Wallis test. The results showed that most of the respondents preferred the fruit with a medium-size, tastes sour but not bitter, has attractive colors, has no pungent flavor, has soft and smooth texture, and is not crispy when it is bitten and chewed. The hedonic test showed that sample #4 and #7 have the highest average value of 4.7. The lowest average obtained in sample #3, where respondents did not like the sample. There was no significant difference of the average. The ranking of hedonic test result indicates the level of respondents' preferences in sequence are Eugenia sp. from Southeast Sulawesi, Myrtus pendula, Syzygium bankense, Syzygium aqueum, Eugenia sp. from Papua, Syzygium sp. from Seram Island, and Syzygium polycephaloides.Keywords: Bogor Botanic Gardens, consumer preference, Myrtaceae fruits, organoleptic test AbstrakBuah jambu-jambuan koleksi Kebun Raya Bogor berpotensi dijadikan buah konsumsi baru. Tujuan penelitian adalah untuk mengetahui dan menilai preferensi serta tingkat kesukaan masyarakat terhadap jenis buah jambu-jambuan koleksi Kebun Raya Bogor. Metode yang digunakan adalah uji organoleptik melalui metode uji deskriptif, uji kesukaan, dan uji rangking. Parameter uji meliputi rasa, warna, aroma, tekstur, suara, dan ukuran. Analisis data dilakukan secara deskriptif dan non-parametrik Kruskal-Wallis. Hasil penelitian memperlihatkan sebagian besar responden menyukai jenis buah berukuran sedang, rasa dominan masam tetapi tidak pahit, warna mencolok, aroma tidak menyengat, tekstur lunak dan halus, serta tidak renyah saat digigit. Hasil uji kesukaan menunjukan nilai rata-rata tertinggi sebesar 4,7 terdapat pada sampel #4 dan #7. Rata-rata terendah ditunjukkan pada sampel #3 sebesar 3,0, yaitu responden tidak menyukai sampel tersebut. Perbedaan rata-rata tersebut tidak signifikan. Perangkingan hasil uji kesukaan menunjukkan tingkat kesukaan responden secara berturut-turut adalah Eugenia sp. asal Sulawesi Tenggara, Myrtus pendula, Syzygium bankense, Syzygium aqueum, Eugenia sp. asal Papua, Syzygium sp, asal Pulau Seram, dan Syzygium polycephaloides.Kata kunci: buah jambu-jambuan, Kebun Raya Bogor, preferensi konsumen, uji organoleptik